Emigration in Konstanty Gaszyński’s articles published in “Le Mémorial d’Aix” - Kowalska, Magdalena (Zagadnienia Rodzajów Literackich, 2022)
The aim of this paper is to describe the presence of the phenomenon of emigration in Konstanty Gaszyński’s French articles published in “Le Mémorial d’Aix” (1837–1841). The Polish writer recalls the November Uprising and the first experiences of his exile in Belgium, he explores Provence as a land of emigration from ages and introduces immigrants other than those of Polish nationality in a world represented through his short stories and press articles. Gaszyński’s main interests focus on historical and urban topics. The content analysis and the remarks about the status of the narrator show that it is the land and culture of Provence that is much often marked by melancholy than the evocation of Polish themes, which are vivid and joyful. Even if more emotional observations about the immigrant life are included, they are indirect, as they are mediated for instance by the voices from precedent ages or mentioned in the footnotes. The presentation leads to the conclusion that the freshness that Gaszyński brings to the Polish Romantic emigration narrative concerns its depiction as less dramatic and sorrowful but also as more universal (e.g., mysterious in the Romantic spirit, experienced not uniquely by the Polish nation) in manner thanks to the combination of two plans, the historical and contemporary, of migration, and his autocreation as the local patriot and the ironic remarks about the rising touristical perspective.